Linking reward-learning and affect in health and depression - Halahakoon, DC (2023)
Relatively little is known about the mechanism underlying major depressive disorder (MDD), necessitating the exploration of novel investigative frameworks. In recent years reward processing has emerged as a promising theoretical framework for investigating depressive symptoms. In parallel, computational modelling has emerged as a promising analysis framework for leveraging the richness of (all manner of) psychiatric data. In this thesis I will use a reward processing framework and computational modelling to investigate a number of areas that are relevant to MDD.